(untitled) (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2014)
The study aimed to know the reasons behind football stadiums rebellion in Jordan From faculty members perspective in faculties of sport education in Jordanian universities. Study sample were 94 member from the faculties of sports education in Jordanian universities, researcher used a questionnaire to collect the data. The results indicated that reasons behind football stadiums rebellion, descending listed : reasons related to Audience, reasons related to players, reasons related to security, related To Referees, reasons related to managers and reasons related to coaches, furthermore there is no difference with Statistically significant in reasons behind stadiums rebellion in Jordan to members of faculty in sports faculties in Jordanian universities strengthening the Variable sensory and Academic Rank. The researcher recommended that the need for all Sports Leadership at all levels of sports management, especially in football and through security leadership and the Association of the masses and the multi-media, through the Committee of referees and coaches, and select suitable members for the administrative bodies down to the players to Provide multiple plans and programs integrated with each other to improve the Athlete behaviour.